2007
DOI: 10.1586/14737175.7.11.1597
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated sodium channel blockers for the treatment of neuropathic pain

Abstract: Pain serves a crucial physiological function, warning the body of impending or actual tissue damage, preventing further damage and aiding the healing process. Neuropathic pain, resulting from nervous system injury or dysfunction, can be a serious medical problem and especially difficult to treat. Although sodium channel blockers are clinically useful for treating pain, they often provide only partial relief and adverse effects associated with nonspecific actions can limit their use. Research on the roles of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 188 publications
(229 reference statements)
0
87
0
Order By: Relevance
“…Of the VGSCs that we tested, Nav1.7 showed the highest sensitivity for HWTX-IV. This is intriguing as Nav1.7 plays crucial roles in the pathophysiology of pain (29, 39 -41), and Nav1.7 blockers could aid the development of new drugs that can effectively treat pain (42). Indeed our preliminary experiments suggest that HWTX-IV can reduce pain behaviors in rats (14) (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Of the VGSCs that we tested, Nav1.7 showed the highest sensitivity for HWTX-IV. This is intriguing as Nav1.7 plays crucial roles in the pathophysiology of pain (29, 39 -41), and Nav1.7 blockers could aid the development of new drugs that can effectively treat pain (42). Indeed our preliminary experiments suggest that HWTX-IV can reduce pain behaviors in rats (14) (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…As summarized in Table 6, Na v 1.7, -1.8, -1.9, and perhaps -1.3 are potential candidate targets for pain therapeutics because of their established role in pain, selective expression in nociceptive neurons and nerve terminals, and/or their regulation in pain states (see reviews by Catterall et al, 2005a;Cummins and Rush, 2007;Dib-Hajj et al, 2009;England and de Groot, 2009;Catterall, 2010;Dib-Hajj et al, 2010). Other Na v types are also expressed in sensory neurons, including Na v 1.1, -1.6, and (at low levels) -1.5 (Catterall et al, 2005a;Catterall, 2010;DibHajj et al, 2010), but inhibition studies with -conotoxins have suggested that Na v 1.6 and Na v 1.7 are the major contributors to peripheral nerve action potentials (Wilson et al, 2011a).…”
Section: F Sodium Channel Inhibition In Pain Managementmentioning
confidence: 99%
“…It is expressed predominantly in small nociceptive primary afferent nerves (Catterall et al, 2005a;Cummins and Rush, 2007;Catterall, 2010;Dib-Hajj et al, 2010). Na v 1.8 contributes to the action potential and repetitive firing in small, nociceptive sensory neurons (Catterall et al, 2005a;Cummins and Rush, 2007;Catterall, 2010;Dib-Hajj et al, 2010).…”
Section: F Sodium Channel Inhibition In Pain Managementmentioning
confidence: 99%
“…This topic is of great ongoing interest in the field, and the reader is referred to additional recent reviews for further reading. [155][156][157][158][159][160][161][162][163][164] …”
Section: Discussionmentioning
confidence: 99%